Experimental Insights into the Cognitive Significance of Early Stone Tools - Moore, Mark W.; Perston, Yinika (PLOS ONE, 2016)
Stone-flaking technology is the most enduring evidence for the evolving cognitive abilities of our early ancestors. Flake-making was mastered by African hominins ~3.3 ma, followed by the appearance of handaxes ~1.75 ma and complex stone reduction strategies by ~1.6 ma. Handaxes are stones flaked on two opposed faces (‘bifacially’), creating a robust, sharp-edged tool, and complex reduction strategies are reflected in strategic prior flaking to prepare or ‘predetermine’ the nature of a later flake removal that served as a tool blank. These technologies are interpreted as major milestones in hominin evolution that reflect the development of higher-order cognitive abilities, and the presence and nature of these technologies are used to track movements of early hominin species or ‘cultures’ in the archaeological record. However, the warranting argument that certain variations in stone tool morphologies are caused by differences in cognitive abilities relies on analogy with technical replications by skilled modern stoneworkers, and this raises the possibility that researchers are projecting modern approaches to technical problems onto our non-modern hominin ancestors. Here we present the results of novel experiments that randomise flake removal and disrupt the modern stoneworker’s inclination to use higher-order reasoning to guide the stone reduction process. Although our protocols prevented goal-directed replication of stone tool types, the experimental assemblage is morphologically standardised and includes handaxe-like ‘protobifaces’ and cores with apparently ‘predetermined’ flake removals. This shows that the geometrical constraints of fracture mechanics can give rise to what appear to be highly-designed stoneworking products and techniques when multiple flakes are removed randomly from a stone core.